Let f(x)= -3 x+ 7 and g(x)=18 x+1. a) g(x)-f(x)= b) f(x)g(x) = c) g(f(x))

Algebra
Tutor: None Selected Time limit: 1 Day

how do I do this question confused. 

Nov 8th, 2014

a) 18x-1-(-3x+7) = 18x-1+3x-7 = 21x-8

b) (-3x+7)(18x+1)= -54x^2-3x+126x+7 = -54x^2+123x+7

c) 18(-3x+7)+1 = -54x+126+1= -54x+127

Nov 8th, 2014

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Nov 8th, 2014
...
Nov 8th, 2014
Dec 4th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer